2008
DOI: 10.1063/1.2987485
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional optical antennas: Nanocones in an apertureless scanning near-field microscope

Abstract: A sharp-tipped gold nanocone and the vertically aligned metallic tip of a near-field optical microscope together form a three-dimensional optical antenna with a highly controllable gap. Confocal measurements with different laser modes show the efficient axial excitation of the cones with a longitudinally polarized field. In the antenna configuration, extremely strong field enhancement up to a factor of 100 is obtained by tuning the gap between the two sharp tips down to few nanometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 21 publications
2
76
0
1
Order By: Relevance
“…The fitted curve shows that the CAS signal has a cos 6 (q) scattering dependence, which demonstrates that the CAS signal originates from a third-order nonlinear process, in agreement with observations by Kim et al [17] We also verified the imaging capability of nanoscale gold structures by generating coherent anti-Stokes signals from patterned nanoparticle assemblies. Here, the sample was prepared by drying a droplet of the GNR solution on a piece of silicon wafer, which caused the formation of irregular patterns in the interior of the dried spot.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The fitted curve shows that the CAS signal has a cos 6 (q) scattering dependence, which demonstrates that the CAS signal originates from a third-order nonlinear process, in agreement with observations by Kim et al [17] We also verified the imaging capability of nanoscale gold structures by generating coherent anti-Stokes signals from patterned nanoparticle assemblies. Here, the sample was prepared by drying a droplet of the GNR solution on a piece of silicon wafer, which caused the formation of irregular patterns in the interior of the dried spot.…”
Section: Resultssupporting
confidence: 85%
“…CAS imaging visualized evenly distributed GNRs and the intensity of the CAS signal was proportional to the square of the particle number density. When GNRs were regularly oriented, the CAS signal was demonstrated to show a cos 6 (q) dependence on the angle between the polarization of the excitation beams and the longitudinal axis of the GNRs. This relationship confirmed that CAS emission by GNRs was a nonlinear, third-order process and that the CAS signal originated from the excitation of surface plasmon resonances in the nanorods.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These aggregates have very promising potentials in applications like biosensing, [58,59,60] subwavelength waveguiding, [61,62] metamaterial applications, [63,64,65] imaging and fluorescence applications, [66,67,68] This coupling depends on wire-substrate separation and the dielectric permittivity of the substrate. For strongly absorbing substrates, the substrate-induced damping can be very large.…”
Section: Chapter 6 Conclusionmentioning
confidence: 99%